THE IMPACT OF OCCUPATIONAL HEALTH AND SAFETY ON EMPLOYEE PRODUCTIVITY: A SYSTEMATIC LITERATURE REVIEW - Feri Andika Prasetya; Sopiah; Arief Noviarakhman Zagladi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to systematically examine the impact of Occupational Health and Safety (OHS) on employee productivity by synthesizing evidence from existing literature. The research adopts the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach to ensure a transparent and rigorous review process. A total of 600 articles were initially identified from the Scopus database, and after screening, eligibility assessment, and quality evaluation, 63 relevant studies were selected for analysis. The findings reveal that OHS significantly influences employee productivity through multiple dimensions, including psychosocial factors, technological and environmental conditions, and organizational structures. Effective OHS implementation enhances employee well-being, reduces workplace risks, and improves motivation, engagement, and performance. Furthermore, the integration of safety culture, leadership support, and advanced safety technologies contributes to sustainable productivity outcomes. This study highlights that OHS should not be viewed merely as a regulatory requirement but as a strategic investment that drives organizational efficiency and long-term success. The findings provide important theoretical insights and practical recommendations for policymakers and organizations in designing comprehensive OHS strategies.